I Have to Make an Effort to Maintain My Structure, Otherwise I Melt - Chauhan, Dinesh (Homœopathic Links, 2014)
The whole idea while searching for the simillimum for the patient is to match the centre of the patient with the centre of the remedy. Here, in this case, the Three Steps of Case Witnessing helps to arrive at the source step by step. Also, for this case, the source is the centre of the case where the patient totally identifies with the source. It completely matches the whole centre of the remedy given and hence it was prescribed to the patient.
Keywords: Passive; Active; and Active-Active case witnessing processes; Nonhuman; Source; Steps of searching the simillimum; Medusa